#### Answer

The answer is $-26$.

#### Work Step by Step

We insert $x = 3$ in $1 - 12x +x^2$:
$1 - 12x +x^2 = 1 - 12 \cdot 3 +3^2 = 1- 36 + 3 \cdot 3 = 1 - 36 + 9 = -26$.

Published by
Wiley

ISBN 10:
1118583191

ISBN 13:
978-1-11858-319-7

The answer is $-26$.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.